Familial Exudative Vitreoretinopathy: A Case Report: Doi: 10.36351/pjo.v40i2.1527 - Tayyab, Mashal; Kashif Iqbal; Awaid Abid (Pakistan Journal of Ophthalmology, 2024)
Familial Exudative Vitreoretinopathy (FEVR), also known as Chriswick Schepens Syndrome is an inherited condition characterized by failure of vascularization of retinal periphery. This results in variable clinical manifestations such as telangiectasia, hemorrhage, exudation, retinal traction and detachment. Presented herein is a case of a14 year old female who exhibits decrease of vision in right eye since 6 months. Examination shows dragging of disc with tractional band at macula and telangiectatic vessels in temporal retinal periphery. Based on detailed history, clinical examination and investigations, a diagnosis of FEVR is made.